2013
DOI: 10.1080/17458080.2012.733078
|View full text |Cite
|
Sign up to set email alerts
|

In vivomodulatory effects of chitooligosaccharide nanoparticles on mouse serum cytokines and splenocytes

Abstract: Water-soluble chitosan derivative-based nanoparticles (carboxymethyl chitosan-chitooligosaccharide nanoparticles (CMC-COS NP) and sulphated chitosan-chitooligosaccharide nanoparticles (SC-COS NP)) were prepared by the formation of polyelectrolyte complexes. SC-COS NP and CMC-COS NP both induced the proliferation of mouse fibroblasts, whereas they elicited dose-dependent inhibitory effects on the proliferation of both HeLa and mouse B16 melanoma cells. Injection of SC-COS NP and CMC-COS NP modulated serum Th cy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…8,9 Although in a study by Minami et al, chitooligosaccharide nanoparticles have been reported to elicit a better immune response compared to the chitooligosaccharides per se. 10 Nevertheless, the mechanism of action for chitosan nanoparticle (CSNP) and its oligosaccharide has been poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 Although in a study by Minami et al, chitooligosaccharide nanoparticles have been reported to elicit a better immune response compared to the chitooligosaccharides per se. 10 Nevertheless, the mechanism of action for chitosan nanoparticle (CSNP) and its oligosaccharide has been poorly understood.…”
Section: Introductionmentioning
confidence: 99%
“…COS reduced OGT-related NF- κ B O-GlcNAcylation and so inhibited LPS-mediated inflammation of the vascular endothelia [60]. Polar chitosan formulation based on nanoparticles CMC-COS NP and SC-COS NP was produced by the development of complexes of polyelectrolyte [61]. Injection of CMC-COS NP and SC-COS NP changed Th cytokine content in blood and induced the differentiation of lymphocytes in spleen in vivo , approving their ability to control cell-induced immune reactions.…”
Section: Resultsmentioning
confidence: 99%